Prevalencia de biotipos gingivales según seibert y lindhe en pacientes con dentición permanente atendidos en la unidad de segunda especialización en estomatología (USEE) - UNT, 2015 - Arbildo Vega, Heber Isac (2015)
The purpose of this study was to determine the prevalence of gingival biotypes according Seibert and Lindhe in patients with permanent dentition treated in the Second Unit Specialization Stomatology (USEE) - UNT during 2015. This is an observational study, descriptive and cross which was carried out in the dental clinic USEE National University of Trujillo, during the months of January to June 2015. The sample consisted of 286 patients who were underwent an analysis of the gingival biotype, the amount of interdental papilla and dental form using a WHO periodontal probe type and recording data on a special form for this purpose. For comparison of the gingival biotype with interdental papilla height, tooth shape and gender Chi square test was used for comparison and the gingival biotype with age the Mann Whitney U test was used. Statistical significance was 5%. It was ultimately determined that the prevalence of gingival biotype by Seibert and Lindhe was 61.2% for thick gingival biotype and 38.8% for the thin gingival biotype. Furthermore, these results show that the gingival biotype is intimately related to gender, the height of the interdental papilla, tooth shape and age